Too Important for the Generals : How Britain Nearly Lost the First World War - Mallinson, Allan (London Bantam Books, 2017)
'War is too important to be left to the generals' snapped future French prime minister Georges Clemenceau on learning of yet another bloody and futile offensive on the Western Front. One of the great questions in the ongoing discussions and debate about the First World War is why did winning take so long and exact so appalling a human cost? After all this was a fight that, we were told, would be over by Christmas. Now, in his major new history, Allan Mallinson, former professional soldier and author of the acclaimed 1914- Fight the Good Fight, provides answers that are disturbing as well as controversial, and have a contemporary resonance. Mallinson argues that from day one of the war Britain was wrong-footed by absurdly faulty French military doctrine and paid, as a result, an unnecessarily high price in casualties. He shows that Lloyd George understood only too well the catastrophically dysfunctional condition of military policy-making and struggled against the weight of military opposition to fix it. And he asserts that both the British and the French failed to appreciate what the Americans' contribution to victory could be and, after the war, to acknowledge fully what it had actually been.
Include Illustrations and Index
Keywords: War--Causes -- World War, 1914-1918